EFFECT OF EXPORT-IMPORT OF OIL AND GAS COMMODITIES ON FOREIGN EXCHANGE RESERVES IN INDONESIA - Sri Setiawati, Ririt Iriani; Harpy, Meyva (JEA17: Jurnal Ekonomi Akuntansi, 2023)
Foreign exchange reserves are an important tool and source of financing for the state for national development. Changes in the value of the country's foreign exchange reserves are influenced by several factors, one of which is export-import activities. This study aims to analyze the effect of oil and gas exports and imports comodity on Indonesia's foreign exchange reserves in 2013-2022. The analytical method used in this study is multiple linear regression analysis. The data source used is a secondary time series data source obtained from the Central Bureau of Statistics (BPS). Data processing is done with the help of a computer application, namely the SPSS program. The results of the study show that Oil and Gas Exports (X1) and Oil and Gas Import Variables (X2) have a significant effect on Indonesia's Foreign Exchange Reserves for 2013- 2022.